A influência da capacidade absortiva no desempenho de empresas de tecnologia da informação - Cardozo, Claudio Testoni (Universidade do Vale do Rio dos Sinos, 2018)
This master’s thesis refers to the adaptability of information technology companies to turbulent environments, whether due to political and financial crisis, or even by the peculiar characteristic of an environment in constant change and increasingly innovations. This ability to change quickly amid an uncertain environment is deepened by the firm's dynamic capabilities. Information technology companies are recognized by the literature as knowledge intensive business, where the absorptive capacity is revealed as a mechanism that fosters innovation and performance. Seeking a better comprehension of this theme, this research evaluates the relationship between absorptive capacity’s elements and organizational performance’s elements in IT companies. For this purpose, a theoretical model, which included hypotheses relating those relationships, was created and submitted through the application of the technique of structural equation modeling. The results of this analysis were submitted to an expert’s panel who analyzed the model’s supported hypotheses and contributed with discourses that revealed a set of competencies and mechanisms that explain how the absorptive capacity is operationalized in those organizations. The final result showed not only the relationship between the elements of the absorptive capacity (acquisition, assimilation, transformation and exploration) with the performance but also the relationships between this model in other revealed aspects: (i) Competitiveness; (ii) Strategy; (iii) Networking; (iv) Economic and political environment; (v) Organizational learning; and (vi) Organizational climate. The results also suggest the realization of future longitudinal researches for analysis and comparison at different moments.
Keywords: Capacidade absortiva; Capacidades dinâmicas; Aprendizagem organizacional; Desempenho organizacional; Gestão do conhecimento; Absorptive capacity; Dynamic capabilities; Organizational learning; Organizational performance; Knowledge management; ACCNPQ::Ciências Sociais Aplicadas::Administração